Pengembangan Bahan Ajar Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Strategi Pembelajaran - Satutik Rahayu; Ahmad Harjono; Gunawan Gunawan (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
Teaching material is one important factor that influences the effectiveness of the learning process. The purpose of this research is to develop teaching materials that have been tested for validity and are suitable for use and to test whether the use of teaching materials that have been developed can increase the value of learning outcomes. This research is a Research and Development (R&D) research with reference to the development of Four D (4 D) which includes Define, Design, Develop and Disseminate. The research subjects are the fourth semester students taking Physics learning strategy courses. Improved learning outcomes in the test using the Normalized N-Gain test. The results showed that the teaching materials of learning strategies that have been developed have been tested for validity and are feasible to be used, while the N-Gain test results show that 0.67% is in the medium category level and an increase in student learning outcomes.